The ring legends of Tolkien : an illustrated exploration of rings in Tolkien's world, and the sources that inspired his work from myth, literature and history /: an illustrated exploration of rings in Tolkien's world, and the sources that inspired his work from myth, literature and history. (2020) - Day, David, 1947-
No abstract available